Core temperature measurement goes high tech - Schnirring, L. (The Physician and Sportsmedicine, 2004)
Recent, high-profile heat illness deaths in professional sports have heightened interest in technological tools that can prevent future fatalities. A pill sensor that can wirelessly transmit a patient's core body temperature, used for years in research laboratories and in the space program, is now poised for use on the sidelines and at other activity events and explained in this article.